Post-conflict Policies in Colombia. An approach of the potentiality of South-South Cooperation (SSC) in the peace process (2018)
The agreement between the Colombian government and FARC-EP insurgency is an important milestone towards the resolution of one of the longest civil conflicts in history. However, there are several issues that have not been completely addressed: disarmament, reinsertion of former combatants, political participation and justice. Taking into account these needs, South-South Cooperation (SSC) becomes relevant, especially as it targets technical and participatory assistance rather than just direct money transfers. In this context, the article has three purposes: firstly, it analyzes the post-conflict policies implemented up-to-date. Secondly, it investigates specific policies coming from SSC sources. And jmally, it extrapolates SSC initiatives from other Latin American countries that have endured similar conflicts. It is concluded that, though SSC is inspiring post-conflict policies in Colombia, there are some other unexplored prospects that could be useful. Key words: Post conflict, Peace agreement, SSouth-South Cooperation, FARC-EP, Colombia.